2015
DOI: 10.1007/s11682-015-9413-5
|View full text |Cite
|
Sign up to set email alerts
|

Is the Alzheimer’s disease cortical thickness signature a biological marker for memory?

Abstract: Recent work suggests that analysis of the cortical thickness in key brain regions can be used to identify individuals at greatest risk for development of Alzheimer’s disease (AD). However, it is unclear to what extent this “signature” is a biological marker of normal memory function – the primary cognitive domain affected by AD. We examined the relationship between the AD signature biomarker and memory functioning in a group of neurologically healthy young and older adults. Cortical thickness measurements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 33 publications
4
26
0
Order By: Relevance
“…These have important implications for healthy aging, as AD signature cortical thickness (comprising the inferior and middle temporal lobes, entorhinal cortex, and fusiform gyrus) is integral to memory function, and atrophy in these regions is an early biomarker of mild AD [25]. Busovaca et al (2016) found AD signature cortical thickness to be associated with memory performance in younger and healthy older adults similarly, and that age group differences in memory performance were mediated by regions of AD signature cortical thickness [40]. Moreover, asymptomatic individuals with fibrillar forms of amyloid have cortical thinning in regions of AD signature cortical thickness compared with individuals without evidence of amyloid, suggesting that the degree of cortical thinning in regions of AD signature cortical thickness predicts progression to clinical AD among cognitively healthy older adults [39,41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These have important implications for healthy aging, as AD signature cortical thickness (comprising the inferior and middle temporal lobes, entorhinal cortex, and fusiform gyrus) is integral to memory function, and atrophy in these regions is an early biomarker of mild AD [25]. Busovaca et al (2016) found AD signature cortical thickness to be associated with memory performance in younger and healthy older adults similarly, and that age group differences in memory performance were mediated by regions of AD signature cortical thickness [40]. Moreover, asymptomatic individuals with fibrillar forms of amyloid have cortical thinning in regions of AD signature cortical thickness compared with individuals without evidence of amyloid, suggesting that the degree of cortical thinning in regions of AD signature cortical thickness predicts progression to clinical AD among cognitively healthy older adults [39,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…AD signature cortical thickness, including cortical thinning in the inferior temporal lobes, middle temporal lobes, entorhinal cortex, and fusiform gyrus, has been used as a general indicator of AD-associated neurodegeneration [25]. It is associated with memory performance, cognitive decline, and progression to dementia [39][40][41][42][43][44], and is a better predictor of progression from mild cognitive impairment (MCI) to AD than hippocampal volume [45]. It is also closely associated with AD-like CSF characteristics [37].…”
Section: Introductionmentioning
confidence: 99%
“…It is of common use for the diagnosis of neurodegenerative diseases such as Alzheimer's disease [1][2][3]. The brain atrophy can be estimated from the measure of the cortical thickness [4,5].…”
Section: Medical Imaging Applicationmentioning
confidence: 99%
“…This technique is of major interest in the context of neurodegenerative diseases such as Alzheimer's disease [1][2][3]. By measuring the cortical thickness of the brain, it is possible to estimate the brain atrophy that is considered as a crucial marker of neurodegeneration in Alzheimer's disease [4,5]. Previous works have already studied measures of central tendency of biomarkers of the brain activity.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that a cortical thickness AD signature measure, comprised of nine regions of interest (ROIs), is a valid reflection of AD continuum severity and is reliable across multiple samples including those scanned at different field strengths [17] . Moreover, we have shown that it is associated with memory performance, cognitive decline, and progression to dementia [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , is a better predictor of progression from mild cognitive impairment (MCI) to AD compared to entorhinal [18] or hippocampal volume [24] , and is closely associated with AD-like CSF characteristics [22] .…”
Section: Introductionmentioning
confidence: 99%